Youth hawkerprise campaign - Aw, Wendy Wen Ting (2014)
This paper presents the Youth Hawkerprise Campaign, the first-ever communication campaign in Singapore to encourage youths to join the hawker trade, organised by four final year students from the Wee Kim Wee School of Communication and Information. Targeted at youths aged 17-35, this campaign aims to raise awareness of the lack of youths in the hawker trade and challenge negative hawker stereotypes by utilising positive images and success stories of existing youth hawkers. Focusing on interactive platforms such as a photo exhibition and a workshop with networking opportunities, the campaign strives to provide opportunities for youths with the passion in culinary arts to consider the potential of honing their abilities and setting up a viable food business at a hawker centre. It seeks to keep the street food culture in Singapore alive and ensure that affordable dining will be available for generations of Singaporeans to come. This paper summarises the primary and secondary research that formulated key campaign strategies. It outlines the process from creative conception to execution of the campaign initiatives and examines the campaign’s tactical effectiveness through extensive evaluative measures. Evaluation includes pre- and post-campaign surveys, metrics from online and mass media publications, as well as an analysis of all media coverage. This report also provides future recommendations for the continuation of the campaign’s pioneering initiatives in the hawker industry. Detailed appendices that support the main text with precise graphs, tables and charts as well as original collateral designs are accompanied for further reference.